A Thermochemical Route to the Sustainable Upgrade of Plastic Solid Waste Using Iron as a Catalyst Precursor - Letizia Marchetti; Cristiano Nicolella; Leonardo Tognotti; Szymon Doszczeczko; Roberto Volpe (Chemical Engineering Transactions)
The management of plastic solid waste represents a significant challenge due to the rapid growth in plastic production and its inherent non-biodegradable nature. Pyrolysis appears as a promising alternative to landfilling and incineration, consisting of a thermal decomposition of feedstock in a sub-stoichiometric-oxygen environment, thus giving rise to three phases: a solid one (pyro-char), liquid, and gas. Although most works focus on optimizing (e.g. maximizing the yield or improving the quality of) the liquid and gaseous fractions, the pyro-char has not been given sufficient attention, despite its potential application in numerous desirable fields.